2016
DOI: 10.1002/iub.1511
|View full text |Cite
|
Sign up to set email alerts
|

Circulating serum irisin levels in obesity and type 2 diabetes mellitus

Abstract: Irisin is an exercise-regulated myokine inducing browning of white adipose tissue and has gained interest as a potential new strategy to combat obesity and its associated disorders, such as type 2 diabetes mellitus (T2DM). The aim of this study is to evaluate the circulating serum irisin levels in obesity and T2DM and also to elucidate possible relationships between serum irisin levels with anthropometric and metabolic parameters of obesity and T2DM. One hundred fifty newly diagnosed T2DM patients as well as 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
84
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 48 publications
14
84
0
2
Order By: Relevance
“…Of particular interest in this context is irisin, a newly identified adipomyokine derived from fibronectin type III domain containing 5 (FNDC5), which has gained attention for its potential in the prevention and treatment of obesity and T2DM [6,7]. In this regard, the circulating levels of irisin were found to be altered in obese individuals and diabetic patients [8]; these levels were considered to be one biomarker for the prediction of the development of diabetes and mortality risk of cardiovascular diseases [9,10]. We and others have demonstrated that, in an overnutrition state, irisin can restore metabolic homeostasis, thereby alleviating insulin resistance and protecting cell function as well as survival in hepatic tissues [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in this context is irisin, a newly identified adipomyokine derived from fibronectin type III domain containing 5 (FNDC5), which has gained attention for its potential in the prevention and treatment of obesity and T2DM [6,7]. In this regard, the circulating levels of irisin were found to be altered in obese individuals and diabetic patients [8]; these levels were considered to be one biomarker for the prediction of the development of diabetes and mortality risk of cardiovascular diseases [9,10]. We and others have demonstrated that, in an overnutrition state, irisin can restore metabolic homeostasis, thereby alleviating insulin resistance and protecting cell function as well as survival in hepatic tissues [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Irisin also mediates the beneficial metabolic effects of exercise and has a potentially favorable effect on obesity and diabetes. Previous studies have reported that the serum level of irisin is positively related to the body mass index (4,5) and serum fatty acid profile (5)(6)(7)(8). However, the relationship between irisin and glucose metabolism is quite complicated, and results concerning the correlation between irisin and fast insulin have been controversial (9)(10)(11).…”
mentioning
confidence: 99%
“…Irisin is a novel hormone (myokine) secreted by cardiac and skeletal myocytes in response to exercise that may regulate metabolism and limit weight gain, although its precise role is controversial (106, 107). Circulating levels of irisin are reported to be reduced or increased in obese subjects, but reduced in type 2 diabetic patients (106, 108, 109). Lower levels of irisin are associated with endothelial dysfunction (109, 110).…”
Section: Potential Targets or Approachesmentioning
confidence: 99%